PENGARUH UKURAN PERUSAHAAN, INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Safitri Dwi Pertiwi; Desy Purwasih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to prove empirically about the effect of firm size, fixed asset intensity on tax avoidance with sales growth as a moderating variable. The independent variables used in this study are firm size and fixed asset intensity, while the dependent variable is tax avoidance. This study also uses a moderating variable in the form of sales growth. It aims to find a stronger influence between the independent and dependent variables by including the moderating variable. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. The sample selection method used purposive sampling, based on this method, 8 companies were obtained with research for 6 years, so that 48 observation data were obtained. The data used in this study is secondary data in the form of annual financial reports on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. Based on the results of the study, it shows that the size of the company, the intensity of fixed assets have a simultaneous effect on tax avoidance. Firm size has an effect on tax avoidance. The intensity of fixed assets has no effect on tax avoidance. Sales growth is not able to moderate the effect of firm size on tax avoidance. Sales growth is not able to moderate the effect of fixed asset intensity on tax avoidance